Pemanfaatan Ekstrak Etanol Teh Hijau (Camellia sinensis L.) sebagai Chelating Agent Logam Berat Cu dengan Metode SSA: Utilization of 96% Ethanol Extract of Green Tea (Camellia sinensis L.) as Chelating Agent For Heavy Metal of Cu With AAS Method - Lindawati, Novena Yety; Anggraini, Riska (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
This research was conducted to determine the ability of ethanol extract of green tea (Camellia sinensis L.) as a chelating agent for heavy metal of Cu. Green tea extraction was carried out by maceration method using 96% ethanol solvent. The ethanol extract of green tea was further tested for phytochemical screening. Analysis of the reduction in total heavy metal content of 10 ppm Cu was measured with an Atomic Absorption Spectrophotometer (AAS) at a wavelength of 324,8 nm. The ethanol extract of green tea (Camellia sinensis L.) was made in series of concentrations of 3 ppm, 6 ppm, 12 ppm and 15 ppm. The results showed that ethanol extract of green tea (Camellia sinensis L.) containing alkaloids, flavonoids, phenolics, tannins, saponins and triterpenoids. The average concentration value of ethanol extract of green tea in reducing Cu metal up to 50% (EC50) was 12,26 ppm with coefficient of variation 0,26%.